1995
DOI: 10.1007/bf01454028
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5?-nucleotidase is expressed by pericytes and fibroblasts in the rat heart

Abstract: Ecto-5'-nucleotidase is anchored at the outer surface of cell membranes and thus its reaction product adenosine is released into the extracellular space. Extracellular adenosine displays via specific receptors a wide range of physiological effects in heart. There are discrepancies in the literature concerning the distribution of ecto-5'-nucleotidase in heart. Since we suspected that these may be due to technical problems, in the present study on ecto-5'-nucleotidase in rat heart we attempted to circumvent some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The same result was obtained for the aorta and the femoral artery and vein (data not shown). As has been described earlier, 24 Ϫ/Ϫ mice in the presence of levamisole. Intensified staining using the azo dye method and alkaline pH (8.7) revealed that only part of the myocardial capillaries expresses AP.…”
Section: Resultssupporting
confidence: 66%
“…The same result was obtained for the aorta and the femoral artery and vein (data not shown). As has been described earlier, 24 Ϫ/Ϫ mice in the presence of levamisole. Intensified staining using the azo dye method and alkaline pH (8.7) revealed that only part of the myocardial capillaries expresses AP.…”
Section: Resultssupporting
confidence: 66%
“…It was found that significant animal species differences exist with respect to the cellular localization of the enzyme (Borgers and Thone 1992). Pericytes as well as fibroblasts have been reported to stain particularly positive for ecto-5′-nucleotidase (Borgers and Thone 1992;Mlodzik et al 1995). Results on endothelial cells show a high degree of variability.…”
Section: Estimates Of the Different Sources Of Adenosinementioning
confidence: 89%
“…Results on endothelial cells show a high degree of variability. Ecto-5′-nucleotidase was localized on endothelial cells from resistance arterioles, while for capillary endothelial cells only a weak immunoreaction was reported (Werner and Schunke 1989;Borgers and Thone 1992;Mlodzik et al 1995). On endothelial cells from lymph vessels, however, rich enzymatic activity has been documented (Werner and Schunke 1989;Kato 1990).…”
Section: Estimates Of the Different Sources Of Adenosinementioning
confidence: 90%
“…For example, in the mature brain it is mainly associated with astroglia and only exceptionally with nerve terminals (Zimmermann et al 1993). In the rat heart the enzyme was immunodetected at interstitial cells identified as pericytes or fibroblasts but not at cardiomyocytes (Mlodzik et al 1995). All these data suggest that careful biochemical analyses are required to define the enzyme species participating in extracellular nucleotide metabolism at the surface of a given cell or within defined tissue compartments.…”
Section: Overlapping Tissue Distributionmentioning
confidence: 93%